Images in the making art, process, archaeology - Danielsson, Ing-Marie Back; Jones, Meirion Andrew (Social archaeology and material worlds., 2020)
This book offers an analysis of archaeological imagery based on new materialist approaches. Reassessing the representational paradigm of archaeological image analysis, it argues for the importance of ontology, redefining images as material processes or events that draw together differing aspects of the world. The book is divided into three sections: 'Emergent images', which focuses on practices of making; 'Images as process', which examines the making and role of images in prehistoric societies; and 'Unfolding images', which focuses on how images change as they are made and circulated. Featuring contributions from archaeologists, Egyptologists, anthropologists and artists, it highlights the multiple role of images in prehistoric and historic societies, while demonstrating that scholars need to recognise their dynamic and changeable character.